Working class : challenging myths about blue-collar labor - Torlina, Jeff (Lynne Rienner Publishers, 2011)
Jeff Torlina challenges the conventional wisdom about the attitudes of blue-collar men toward their work. Torlina highlights the voices of pipe fitters, welders, carpenters, painters, locomotive assemblers, and factory workers to reveal the complexities, and advantages, of working-class life. These men see blue-collar labor as a desirable alternative to white-collar occupations; their work involves integrity, character, pride, and a connection with being a real man; values that they perceive as lost in white-collar office jobs. The result is a penetrating critique of many commonly held assumptions, and a compelling case for a new understanding of our social class system. -- Book Description.